Savings in transnational households: a field experiment among migrants from El Salvador (2015)
We implemented a randomized field experiment that tested ways to stimulate migrants’ savings in their origin country. We find that migrants value opportunities to exert greater control over financial activities in their home countries. We offered U.S.-based migrants bank accounts in El Salvador, randomly varying migrant control over El Salvador–based savings by offering different accounts across treatments. Migrants offered the greatest degree of control accumulated the most savings. Impacts likely represent increases in total savings; there is no evidence that savings increases were simply reallocated from other savings mechanisms. Enhanced control over home country savings does not affect remittances sent home.